Time-lapse Imaging Reveals Stereotypical Patterns of Drosophila Midline Glial Migration - Wheeler, Scott R. (2011)
The Drosophila CNS midline glia (MG) are multifunctional cells that ensheath and provide trophic support to commissural axons, and direct embryonic development by employing a variety of signaling molecules. These glia consist of two functionally distinct populations: the anterior MG (AMG) and posterior MG (PMG). Only the AMG ensheath axon commissures, whereas the function of the non-ensheathing PMG is unknown. The Drosophila MG have proven to be an excellent system for studying glial proliferation, cell fate, apoptosis, and axon-glial interactions. However, insight into how AMG migrate and acquire their specific positions within the axon-glial scaffold has been lacking. In this paper, we use time-lapse imaging, single-cell analysis, and embryo staining to comprehensively describe the proliferation, migration, and apoptosis of the Drosophila MG. We identified 3 groups of MG that differed in the trajectories of their initial inward migration: AMG that migrate inward and to the anterior before undergoing apoptosis, AMG that migrate inward and to the posterior to ensheath commissural axons, and PMG that migrate inward and to the anterior to contact the commissural axons before undergoing apoptosis. In a second phase of their migration, the surviving AMG stereotypically migrated posteriorly to specific positions surrounding the commissures, and their final position was correlated with their location prior to migration. Most noteworthy are AMG that migrated between the commissures from a ventral to a dorsal position. Single-cell analysis indicated that individual AMG possessed wide-ranging and elaborate membrane extensions that partially ensheathed both commissures. These results provide a strong foundation for future genetic experiments to identify mutants affecting MG development, particularly in guidance cues that may direct migration. Drosophila MG are homologous in structure and function to the glial-like cells that populate the vertebrate CNS floorplate, and study of Drosophila MG will provide useful insights into floorplate development and function.